Contrasting internal tide turbulence in a tributary of the Whittard Canyon. (1st March 2022) - van Haren, Hans; Mienis, Furu; Duineveld, Gerard
Abstract: Submarine canyons that incise continental slopes are considered an important conduit for transport of suspended matter between shelf seas and deep-ocean. However, the exact mechanisms influencing matter transport and deposition are still largely unknown. We present moored observations of current flows, acoustic echo intensity and, in high-resolution, temperature variation from two contrasting mooring sites 6.5 km apart horizontally in 790 and 1130 m water depth in one of the tributaries incising the flank of the easternmost branch of Whittard Canyon, North-East Atlantic Ocean. The shallow site is situated on a steep thalweg slope which is supercritical for semidiurnal internal tides that have >100 m amplitudes and turbulent overturning evenly distributed over the 240 m range of observations, with no particular intensification near the seafloor. In contrast, the deep site is located on an along-canyon slope that is approximately critical for semidiurnal internal tides, with steeper slopes up-canyon and to the sidewalls. The internal tide amplitude at the deep site is about 75 m. In the lower 100 m, flow intensifies and becomes more rectilinear along the canyon axis, together with intensifying mean turbulence dissipation rate and tidally-averaged down-canyon flow. Over a semidiurnal tidal period three episodes of relatively large turbulence are observed. Turbulence is largest when an upslope moving bore passes. Smaller but still relatively large turbulence is associated with a secondary upslope bore and with strong convective overturning during the downslope tidal phase. The convection is clearly distinguished in temperature variance spectra between the buoyancy and Ozmidov frequencies, the range in which anisotropic stratified turbulence is expected. Averaged over the entire depth-time series, mean turbulent kinetic energy dissipation amounts to 4.4 ± 2 × 10 -7 m 2 s -3, equal for both sites. In the tributary, the first upslope moving bore and the convective overturning at the deep site will affect sediment resuspension most. Highlights: The 240-m and 2-day averaged turbulence above the seafloor is found similar at two sites in a Whittard Canyon tributary. Larger than 100 m waves at the shallow site where the thalweg slope is supercritical for semidiurnal internal tides. Flow intensification near the seafloor at the deep site where the slope is about critical for semidiurnal internal tides. Per tidal period a primary and a secondary bore occur during upslope phase and convective overturning during downslope phase. Primary bore and convective overturning at the deep site reach the seafloor with potential effects for sediment resuspension.